2014
DOI: 10.4028/www.scientific.net/kem.631.357
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Commercial Latex as a Positive Control for <i>In Vitro</i> Testing of Bioceramics

Abstract: Several tests for the biological evaluation of bioceramic materials and medical devices are provided in specific international standards, where in vitro tests have a major role. Tests involving exposure of cells in culture require the use of validated positive controls, which, in the same preparation and treatment conditions, present a substantial and well-known cytotoxicity. The present work aimed to test and validate 3 different sources of low cost, commercially available latex, as positive controls in cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Negative control groups were composed of cells plus culture medium (Alpha-MEM) and polystyrene plus culture medium. Extracts of latex fragments on culture medium were the positive control group, since its consistent cytotoxicity in ISO-based assays was previously demonstrated (10). Each condition was tested using three replicates in each of the three different assays.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Negative control groups were composed of cells plus culture medium (Alpha-MEM) and polystyrene plus culture medium. Extracts of latex fragments on culture medium were the positive control group, since its consistent cytotoxicity in ISO-based assays was previously demonstrated (10). Each condition was tested using three replicates in each of the three different assays.…”
Section: Sample Preparationmentioning
confidence: 99%
“…Figure 5(a) confirms, as expected, that surgical grade titanium and polystyrene are detected as being not cytotoxic, while the latex showed high cytotoxicity, in a dose dependent manner, as expected. However, we can see that the toxicity levels observed for the positive control were much lower than those usually observed in two-dimensional culture, which attain, in the same conditions, cytotoxicity approximately 3 times higher for MC3T3-E1 cells [17]. This lower toxicity may reflect results closer to the clinic, where latex gloves, tourniquets, probes, and tubes are used constantly in direct contact with the body of patients without causing necrosis or actual levels of relevant chronic toxicity or allergy, when not associated with powder [28,29].…”
Section: Resultsmentioning
confidence: 52%
“…As representatives of negative, biocompatible controls, we employed smooth surface machined titanium (SIN Implants, Brazil) and dense beads of polystyrene (INT, Brazil). Amber latex tubes obtained commercially were used as positive controls, since they are known for their increased cytotoxicity [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described for latex, mitochondrial activity is more impacted than cell density and membrane integrity, even though all parameters remained under 25% of cell survival when compared to the control. 23 This multiparametric methodology confirmed that Biodentine is cytocompatible with human bone cells, even when challenged with long-time extractions of possible toxicants. It is not easy to compare the results of different cell culture experiments due to the numerous variations in experimental conditions, such as cell type, cell material contact method, and exposure time.…”
Section: Discussionmentioning
confidence: 59%